Re-casting the Annual Faculty Review - Mark Urtel (Academic Chairpersons Conference Proceedings, 2020)
This session will highlight how one department chair flipped the annual faculty review from a top-down administrative process focused on merit pay to a faculty-centered process focused on professional development and advancement. Following will be discussion on the results of the anonymous survey distributed to faculty from this new process.
Keywords: transparency; faculty; evaluation; annual; review